Coastal proximity and individual living standards: Econometric evidence from geo-referenced household surveys - Frederik Wild; David Stadelmann (Center for Research in Economics, Management and the Arts (CREMA), 2021)
We investigate geo-referenced household-level data consisting of up to 206,896 individuals living in 21,826 localities across 28 sub-Saharan African countries over 20 years. We analyse the relevance of coastal proximity as a predictor of individual economic living standards. Our setting allows us to account for country-time fixed effects as well as individual-specific controls such as age, gender, and most importantly, urbanity. Results reveal that individuals living further away from the coast are more disadvantaged than individuals living in coastal regions along an array of welfare indicators. The findings are robust to the inclusion of other geographic covariates of development such as climate (e.g. temperature, precipitation), elevation or terrain ruggedness. We also explore mechanisms through which coastal proximity may influence individual welfare and decompose the estimated effect of coastal proximity via formal mediation analysis. Our results highlight the role of human capital as well as infrastructural endowments in reconciling the large intra-national disparities in individual economic welfare.
Keywords: O15; O18; R12; O55; 330; Geography; Coastal Proximity; Sub-Saharan Africa; Mediation Analysis